Challenges Faced by Ex-Offenders in Securing Employment in Green Job Sectors: Systematic Literature Review - Fatin Nadirah Khasni; JS Keshminder Singh; S.C. Chuah (Journal of International Business, Economics and Entrepreneurship)
This systematic literature review explores the challenges ex-offenders face in securing employment within the growing green job sector, with a specific focus on studies published in Asia between 2000 and 2014. Guided by the ROSES (Reporting Standards for Systematic Evidence Syntheses) protocol, this study follows a structured and transparent process. Four relevant studies were selected from reputable databases, including Scopus, ScienceDirect, Google Scholar, and BASE-Search. This study identifies several recurring barriers: employer discrimination, limited access to green skills training, weak policy support, and persistent social stigma. These challenges not only reduce employment opportunities for ex-offenders but also hinder broader efforts to build inclusive and sustainable labour markets. The findings offer valuable insights for employers, policymakers, and rehabilitation programs. They emphasize the need for targeted training programs, supportive policies, and fair hiring practices. Ultimately, this study highlights the potential of green jobs as a pathway to successful reintegration, reduced recidivism, and a more socially just and environmentally sustainable society.